THE PRESERVATION OF PECULIARITIES OF LEXICAL AND SEMANTIC ASSOCIATION OF TERMINOGIAL PHRASAL COMPONENTSIN IN INDIRECT TRANSLATION (American Journal of Pedagogical and Educational Research, 2024)
The article discusses the peculiarities of lexical and semantic association of terminological phrasal components used in Ray Bradbury’s stories in English and Uzbek Languages.